PENGUJIAN TEORI AGENSI KEBIJAKAN DIVIDEN DAN STRUKTUR MODAL TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA TAHUN 2016-2021 - Harman Syahfendi; Amin Hou; Debora Tambunan (Jurnal Mahkota Bisnis (Makbis), 2023)
Company performance is one of the most important things in the business world regarding the condition of the company, both internally and externally. It can be explained that company performance is carried out to measure and assess the success of the company's achievements in generating profits, so that the company can see the potential development that the company has achieved. This research aims to test the agency theory of dividend policy and capital structure on company performance in mining companies on the Indonesian stock exchange ( BEI) 2016-2021. The population in this study was 41 mining companies on the Indonesia Stock Exchange 2016-2021. This research used purposive sampling and obtained a sample of 11 companies. The sample collection technique uses a purposive sampling method, namely taking research samples by paying attention to certain criteria based on the research objectives. Data analysis used multiple linear regression with the help of SPSS software. The results of this research show that Dividend policy and Capital Structure simultaneously influence Company Performance (ROA)